1980
DOI: 10.1002/path.1711310302
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of supraclavicular and colonic malakoplakia—A light and ultrastructural study

Abstract: A case of malakoplakia of the supraclavicular region and colon in a 41-year-old patient is presented. Clinical, histopathological, histochemical and ultrastructural features are described. The etiology and pathogenesis are discussed. Malakoplakia is a chronic inflammatory disorder probably due to an abnormal response to infection with Gram negative bacteria, most likely Escherichia coli or Klebsiella. The disease is characterised by the accumulation of macrophages intermixed with plasma cells and lymphocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 56 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…Malakoplakia is a chronic inflammatory disease with disputed etiology and pathogenesis 1 . It is more common in middle-aged females (peak incidence in fifth decade compared with seventh in males) 4 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Malakoplakia is a chronic inflammatory disease with disputed etiology and pathogenesis 1 . It is more common in middle-aged females (peak incidence in fifth decade compared with seventh in males) 4 .…”
Section: Discussionmentioning
confidence: 99%
“…A case of colonic and neck malakoplakia has been reported which responded very well to antibiotics and sulfathiazole 1 . Schmerber et al in 2003 reported a case of cervical malakoplakia, which clinically mimicked a cancer from hypopharynx 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malakoplakia was first introduced in 1902 by Michaelis and Gutmann [1,2]. It is a rare inflammatory condition that is usually found in the urinary tract, mainly in the urinary bladder [3,4].…”
Section: Introductionmentioning
confidence: 99%